Synergistic thermo-oxidative maleation of PA11 as compatibilization strategy for PA6 and PBT blend. (28th September 2019) - Jubinville, Dylan; Chang, Boon Peng; Pin, Jean-Mathieu; Mohanty, Amar K.; Misra, Manjusri
Abstract: The compatibilization of polyamide (PA) 6 and poly(butylene terephthalate) (PBT) blends has been successively achieved by the design of a compatibilizer made from renewable biobased PA11, named PA11C. The synergistic action of maleation coupled with thermo-oxidation of the PA11 backbone allows both improvements of hydrophilic/hydrophobic balance and availability of functional groups that are able to react during the reactive extrusion. The nature of the functional groups was associated to maleic anhydride, terminal vinyl group as well as carbonyls such as aldehydes that come from the PA11 thermo-oxidation cascade reactions. Thermomechanical and morphological investigations corroborate in explaining the compatibilization mechanism probed by multiple reactions in between PA6 and PBT. The toughening effect was observed in the compatibilized PA6/PBT blends through the increase in the elongation at break. This strategy opens new perspectives in term of compatibilization for formulations containing polyester and PA tailored for specific applications. Graphical abstract: Original compatibilization strategy for PA6 and PBT probed by the synergistic action of maleation and thermo-oxidative reactions of PA11.Image 1 Highlights: Successfully designed an original and multifunctional compatibilizer from a biobased PA11. The particle domain size of the PBT phase in the blend decrease with addition of 5 wt% of PA11C, highlighting the compatibilization strategy efficiency. PA11C compatibilizer act as toughening agent for the PA6/PBT blends. Polymer chains in the sub-glass and glass transition exhibit a more homogenous relaxation time distribution, due to reactive compatibilization.